Optimization of Biodiesel Production from Cooking Palm Oil Using Response Surface Methodology (RSM) Approaces - Muhammad Fadhlul Hanin, Ismail (2012)
Biodiesel is one of the renewable energy resource which is suitable to replace the fossil fuel due to the depletion of fossil fuel in the future. The modeling of the design of experiment for optimization of biodiesel production from cooking palm oil is conducted by using Design Expert software version 7.1.6 (Stat Ease). This experimental design is conducted in order to optimize the biodiesel production with significant parameters that affecting the biodiesel production. The parameters that have been used are reaction temperature, methanol to oil molar ratio, catalyst concentration and reaction time. By using response surface methodology (RSM), the optimal parameters levels are determined. The optimum conditions for biodiesel production were at temperature of 72.83°C, alcohol to oil molar ratio of 9.5:1, 3.95% of catalyst concentration and 4.73 hours of reaction time, which was obtained 88.38% of biodiesel yield.